Both the “What” and “Why” of Youth Sports Participation Matter; a Conditional Process Analysis - Gjesdal, Siv; Appleton, Paul R.; Ommundsen, Yngvar (Frontiers in Psychology, 2017)
This study builds on previous research combining achievement goal orientation from Achievement Goal Theory and motivational regulation from Self-Determination Theory. The aim was to assess the combination of the "what" and "why" of youth sport activity, and how it relates to the need for competence and self-esteem. Achievement goal orientation, specifically task and ego, was employed to represent the "what", whilst intrinsic and external regulation reflected the "why". Based on a sample of 496 youth sports participants, structural equation modeling with a bootstrapping procedure was used to examine whether the indirect relationship between achievement goal orientation and self-esteem was conditional to motivational regulation. The results show partial support for the conditional process models. Specifically, task orientation was indirectly linked with self-esteem through competence need, and the relationship was stronger with higher levels of intrinsic regulation for sport. Furthermore, ego orientation was negatively associated with self-esteem through a positive relationship with competence frustration. However, this relationship emerged only for those higher in intrinsic regulation. External regulation did not emerge as a moderator, but presented a positive relationship with competence frustration. Findings are discussed in light of both Achievement Goal Theory and Self-Determination Theory, and underline the importance of considering both the "what" and "why" when attempting to understand motivation in youth sport.